Karakteristik Fisikokimia Dan Sensoris Flakes Berbahan Baku Tepung Jagung (Zea mays L), Tepung Pisang Goroho (Musa acuminafe,sp) dan Tepung Kacang Hijau (Phaseolus radiates) - Meini E. Papunas; Gregoria S.S. Djarkasi; Judith C. Moningka (Universitas Sam Ratulangi, 2013)
ABSTRACTDiversification program conducted by utilizing local food through improved processingtechnology to produce food products. In North Sulawesi, banana goroho a typical localfood, corn is a commodity Manado yellow, and green beans are a source of protein. Thisstudy aims to determine the formulation flakes with corn flour mixture ratio, gorohobanana flour and green bean flour consumers receive. And analyzing the physicochemicalproperties and sensory flakes. This research was conducted at the Laboratory of Foodscience for 3 months. This study uses a completely randomized design with treatmentconcentration ratio mixing cornmeal, flour goroho bananas, green beans and flour.Mixing corn flour 60%, 35% goroho banana flour, mung bean flour 5% is the bestformulation of fisikomia properties and sensory properties. With endurance timecrispness in milk for 4 minutes 47 seconds and the chemical composition of the watercontent of 1.7%, 1.55% ash, 6.59% protein, 3.38% fat, 80.1% carbohydrate. Organoleptictest results show that the resulting flakes can be accepted by consumers of the parametersof taste, flavor, color, and crispness.